Reconquer poetry: a manifesto of creative potency in Art Education (Palíndromo, 2024)
Starting from the experiences and restlessness about the conditions of Art education in the education system in the state of Paraná, the following article has as its goal to relate a cartographic research process already finished and elaborate an analysis, sustained in the articulation between the thought of the philosophers Jacques Rancière, Gilles Deleuze and Félix Guattari, as well as in its approximation with Villém Flusser, that tightens the conceptions experienced and presents possible horizons. To this end, we stem from the distinction between creative act and productive act to think about strategies to transform a precarious education into an emancipatory education, proposing the reconquer of poetry, of the potency of the creative act nonchalant with the productive demands, as a strategy to restructure the conditions of Art education. The path held resulted in a project of exits from the school that reinvented the notions of teaching and learning and provided different relations with artistic practices.
Keywords: cartography; emancipation; art education; poiesis; precariousness